2021
DOI: 10.1021/acsami.0c22295
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Ni2+from the Surface to the Bulk by a New Cathode Electrolyte Interphase Formation on a Ni-Rich Layered Cathode in High-Safe and High-Energy-Density Lithium-Ion Batteries

Abstract: Ni-rich high-energy-density lithium ion batteries pose great risks to safety due to internal short circuits and overcharging; they also have poor performance because of cation mixing and disordering problems. For Ni-rich layered cathodes, these factors cause gas evolution, the formation of side products, and life cycle decay. In this study, a new cathode electrolyte interphase (CEI) for Ni2+ self-oxidation is developed. By using a branched oligomer electrode additive, the new CEI is formed and prevents the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Therefore, we can consider that the BTJ-L polymer coating layer functions also as an artificial CEI layer, impairing TM dissolution from the cathode active materials in the carbonatebased electrolytes. 5,10,41 Figure 9a,b present the Nyquist plots of the coin cells incorporating the pristine NCM811 and 1 wt % BTJ-L@ NCM811 electrodes, conducted at 1C before and after 100 cycles, respectively. Prior to cycling (see Figure 9a), the bulk resistance (R b ) and charge transfer resistance (R ct ) values of the cells containing the 1 wt % BTJ-L@NCM811 electrode (2.5 and 102.2 Ω, respectively) were slightly lower than those of the cells with the pristine NCM811 electrode (3.1 and 122.1 Ω, respectively), likely enabling faster charge carrier transport at high C rates, as revealed in Figure 8a and Table S2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we can consider that the BTJ-L polymer coating layer functions also as an artificial CEI layer, impairing TM dissolution from the cathode active materials in the carbonatebased electrolytes. 5,10,41 Figure 9a,b present the Nyquist plots of the coin cells incorporating the pristine NCM811 and 1 wt % BTJ-L@ NCM811 electrodes, conducted at 1C before and after 100 cycles, respectively. Prior to cycling (see Figure 9a), the bulk resistance (R b ) and charge transfer resistance (R ct ) values of the cells containing the 1 wt % BTJ-L@NCM811 electrode (2.5 and 102.2 Ω, respectively) were slightly lower than those of the cells with the pristine NCM811 electrode (3.1 and 122.1 Ω, respectively), likely enabling faster charge carrier transport at high C rates, as revealed in Figure 8a and Table S2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We conclude that the NCM811 electrode modified with the BTJ-L oligomer additive could effectively alleviate the side reactions between the electrolyte and the electrode, resulting from the inhibition of CEI layer formation in the presence of the BTJ-L protective layer, as revealed in Table S5. 5,10,41,43 Consequently, the electrochemical performance was greatly enhanced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R-Si-O-LiCoO 2 was produced through in situ Co–O bond reinforcement on the surface of LiCoO 2 when LiCoO 2 was in a highly delithiated state. Several studies have indicated that branched oligomers have high potential for absorbing heat during thermal runaway. Thus, in the present study, the amino groups in APTES were made to react with a branched oligomer through the aza-Michael addition reaction to produce an artificial cathode electrolyte interphase (ACEI).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with the accumulation of heat upon long-term and high-power operation, the temperature inside the batteries will exceed 40 °C, leading to the performance decay of batteries. , This places higher demands for the thermal stability of cathodes in LIBs . Currently, Ni-rich layered oxides are the preferred cathodes for high-power LIBs in virtue of their high-energy density. , However, they often undergo inferior thermal stability and rapid resistance growth at high temperatures. Specifically, the electron transfer from O 2 to strong oxidizing Ni 4+ induces lattice oxygen escape, which is further exacerbated by a high temperature. Meanwhile, released oxygen from the lattice framework prefers to react with the electrolytes, thereby exacerbating the interfacial adverse reactions and increasing the resistance. Therefore, synchronously constructing a stable structure and robust cathode–electrolyte interface is crucial for a Ni-rich cathode with enhanced cycling and thermal stability at high temperatures.…”
Section: Introductionmentioning
confidence: 99%